Kinetics of fouling deposit removal of pink guava purees in a cleaning-in-place test rig - Khalid, Nurul Izzah (2015)
Cleaning-in-place (CIP) is an important process in food factories, to maintain a hygienic processing environment. The development of economic CIP requires comprehensive studies of the removal kinetics of the fouling deposit. This work was carried out to investigate the removal kinetics of pink guava puree (PGP) fouling deposits, which to the knowledge of the author has not yet been reported anywhere. This work is divided into three parts which are: (1) design of the cleaning test rig and simulation validation of the design, (2) development of in-situ and ex-situ methods to prepare the PGP fouling deposit, and (3) investigation of the removal kinetics of the PGP fouling deposits by using the cleaning test rig under different cleaning parameters. The design of the lab-scale cleaning test rig was based on the standard design of a recirculating water flow channel. The entry length of 1.016m was determined from computational fluid dynamics (CFD) simulation, which was performed to simulate the cleaning environment in the rig, and to ensure the functionality of the rig was in order before the rig was fabricated. Both methods on developing the physical model of PGP fouling deposit was compared and results have shown than an ex-situ method is a practical method to apply. An ex-situ method was able to form reproducible samples of PGP fouling deposit with low production time and minimal consumptions on raw materials. In part three, only alkaline cleaning stage was considered in this study. The cleaning study was performed at different parameters: temperatures (35-70 °C), fluid velocities (0.6-1.5 m/s) and NaOH concentrations (0-2.0 wt%). Cleaning profiles have shown two stages: rapid and gradual stages. Cleaning response in both stages was investigated by employing an effective removal rate constant, k2. The findings suggested that alkaline rinse can be divided into two stages with the following conditions: (1) conditions for rapid stage are 70 °C, 1.2 m/s, 1.5 wt% NaOH, with trapid=2 minutes; and (2) conditions for gradual stage are 35 °C, 1.5m/s, water (0wt% of NaOH) and with tgradual=10 minutes. The results of the cleaning time suggest that the shortest cleaning time (less than 12 minutes) can be found at 1.5 m/s, 70 °C and with a NaOH concentration of 1.0, 1.5 and 2.0 wt%. Findings from this work suggest two cleaning schemes for alkaline cleaning stage, which classified as 1) economical cleaning scheme and 2) fast cleaning scheme. In economical cleaning scheme, the industries need to identify the rapid and the gradual stage for their cleaning process and this cleaning scheme will reduce the cost on chemicals and utilities. While for fast cleaning scheme, the application of excessive cleaning parameters is needed. However,the cleaning cost is expected to increase significantly.